Does the color of the collar matter? Firm specific human capital and post-displacement outcomes - Guido Schwerdt; Andrea Ichino; Oliver Ruf; Rudolf Winter-Ebmer; Josef Zweimüller (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2008)
We investigate whether the costs of job displacement differ between blue collar and white collar workers. In the short run earnings and employment losses are substantial for both groups but stronger for white collar workes. In the long run, there are only weak effects for blue collar workers but strong and persistent effects for white collars. This is consistent with the idea that firm-specific human capital and internal labor markets are more important in white-collar than in blue collar jobs.
Keywords: J14; J65; 330; Firm Specific Human Capital; Plant Closures; Matching